The Impact of Cultural Norms on Women’s Leadership in Swat: A Feminist Study - Ahmad, Rizwan; Jadoon, Roshan (Majapahit Journal of English Studies, 2025)
Women's leadership is one of the major concerns of the current time in Swat, Khyber Pakhtunkhwa (KPK). A significant number of studies have been conducted regarding women and challenges faced by women in Swat but lesser focus is given to the impact of cultural norms on women's leadership, which needs to be addressed thoroughly. This study aims to explore the impact of cultural norms on women's leadership in Swat KPK. The study is qualitative in nature and carried out with a feminist lens. Moreover, the data were collected from four different women leaders in Swat. After the thematic analysis of the data, the study shows that women are under the influence of cultural norms that are socially constructed in Swat. Furthermore, in some cases, those norms are advantageous but at the same time also create hurdles for women to reach a high position as women leaders.